Gasification of biomass for electricity generation in the Cuban context - Pedroso, Daniel Travieso; Aiello, Ramon Cala (Revista Ciências Exatas, 2008)
The Biomass energy is now accepted as having the potential to provide the major part of the projected renewable energy provisions of the future in order to contribute to the sustainable development of our world. The biomass gasification is one of the most efficiently form to use the energy from biomass. We analyze a Cuban biomass potential for use in the gasification process for the electricity generation as case of study and pay special attention to the technology for electricity production with medium power caloric gas from a new tar free downdraft gasifier.